1993
DOI: 10.1073/pnas.90.15.6924
|View full text |Cite
|
Sign up to set email alerts
|

Folding pathway mediated by an intramolecular chaperone.

Abstract: The N-terminal propeptide of subtilisin, a serine protease, functions as an intramolecular chaperone which is crucial for proper folding of the active enzyme. This nascent N-terminal propeptide is removed after completion of the folding process. Here we present a possible pathway by which intramolecular chaperones mediate protein folding. Using circular dichroism to analyze acid-denatured subtilisin we have identified a folding-competent state which can refold to an active conformation in the absence of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 22 publications
4
63
0
Order By: Relevance
“…The authors suggested that the pro region permits folding to occur at a measurable rate by lowering the free energy barrier separating the denatured state from the thermodynamically more favored native state. Similar findings have been presented for carboxypeptidase Y (Smensen et al, 1993) and subtilisin (Eder et al, 1993;Shinde et al, 1993). However, AChE lacks a pro region (Maulet et al, 1990), and kinetic trapping of AChE in the MG state must be due to some other reason.…”
Section: Spectral Characteristics Of Thermally Denatured Achesupporting
confidence: 73%
“…The authors suggested that the pro region permits folding to occur at a measurable rate by lowering the free energy barrier separating the denatured state from the thermodynamically more favored native state. Similar findings have been presented for carboxypeptidase Y (Smensen et al, 1993) and subtilisin (Eder et al, 1993;Shinde et al, 1993). However, AChE lacks a pro region (Maulet et al, 1990), and kinetic trapping of AChE in the MG state must be due to some other reason.…”
Section: Spectral Characteristics Of Thermally Denatured Achesupporting
confidence: 73%
“…[32][33][34][35] The uncleaved, contiguous propeptide functions at only one point in the folding pathway: assisting in protein folding and stabilization prior to protein maturation. 32 These chaperones remain attached to the mature sequence until the maturation process is complete, and then are proteolytically removed by autoprocessing or another endopeptidase. 32 Analogous to other intramolecular chaperones, the lengthy propeptide (741 aa) of VWF appears to stabilize the intramolecular disulfide interactions between cysteines within individual D1, D2, and D3 domains.…”
Section: Discussionmentioning
confidence: 99%
“…32 These chaperones remain attached to the mature sequence until the maturation process is complete, and then are proteolytically removed by autoprocessing or another endopeptidase. 32 Analogous to other intramolecular chaperones, the lengthy propeptide (741 aa) of VWF appears to stabilize the intramolecular disulfide interactions between cysteines within individual D1, D2, and D3 domains. It is our hypothesis that the propeptide of VWF functions during the maturation process as an intramolecular chaperone.…”
Section: Discussionmentioning
confidence: 99%
“…A growing family of membrane and secretory proteins contain pro-domains at the N-terminal end that undergo post-translational proteolytic cleavage in the late secretory pathway after the protein has acquired transport competence (26,(33)(34)(35)(36). These domains, called intramolecular chaperones, modulate the folding of this class of proteins directly through interaction with other regions of the protein or by substituting for ER resident chaperones.…”
Section: Expression Of a Full-length Im-mentioning
confidence: 99%